H\(_2\)O\(_2\) production in Lactobacillus strains isolated from the intestinal microbiome of healthy people - Thu, Ha Thi; Hung, Hoang The; Thach, Tran Xuan; Hoa, Nguyen Thi; Lan Anh, La Thi; Hien, Vu Thi; Duy, Nguyen Dinh; Quyen, Dong Van; Tuyet Nhung, Nguyen Thi (Academia Journal of Biology, 2020)
Lactobacillus sp. in the digestive tract are capable of producing H2O2 to inhibit the growth of harmful bacteria and balance the gut microflora. In this study, we have isolated 115 strains of Lactobacillus spp. from stool samples of healthy people in Ha Noi. Of the 50 tested Lactobacillus strains, 9 strains were capable of producing H2O2, of which the Lac.VFE-14 strain produced highly H2O2 with a concentration of 2.183 mM, followed by Lac.VFE-08 strains (2.081 mM) and Lac.VFE-04 (2.067 mM). All three strains grew well in MRS medium supplemented with bile salts or adjusted to low pH value. With 0.3% of bile salt, the survival rates of these 3 strains were 99%, 95% and 97%, respectively. At pH 3.0, after 3 hours of cultivation, the survival rates of the three strains were 98.54%, 94.15% and 95.27%, respectively. In addition, each of the cell-free culture supernatants of these three strains that inhibit the growth of S. aureus ATCC-23235. The inhibition zone diameters of the three strains were 19.0±1.0 mm, 14.0±1.0 mm and 11.7±1.3 mm, respectively. The results of 16S rRNA gene analyses showed that Lac.VFE-14, Lac.VFE-08 and Lac.VFE-04 had high similarity scores with L. plantarum ZZU 23 (100%), L. rhamnosus JCM 1136 (99%) and L. plantarum S7 (98.65%), respectively. This study indicates that all three strains have the potential to be used as probiotics in the future.